Modeling the magnetoelectric effect in laminated composites using Hamilton's principle. (11th January 2018) - Zhang, Shengyao; Zhang, Ru; Jiang, Jiqing
Abstract: Mathematical modeling of the magnetoelectric (ME) effect has been established for some rectangular and disk laminate structures. However, these methods are difficult in other cases, particularly for complex structures. In this work, a new method for the analysis of the ME effect is proposed using a generalized Hamilton's principle, which is conveniently applicable to various laminate structures. As an example, the performance of the rectangular ME laminated composite is analyzed and the equivalent circuit model for the laminate is obtained directly from the analysis. The experimental data is also obtained to compare with the theoretical calculations and to validate the new method. Compared with Dong's method, the new method is more accurate and convenient. In particular, the equivalent circuit for the rectangular laminated composite can be obtained more easily by the proposed method as it does not require the complex treatment used in Dong's method.